Beyond Clinical Care: The Role of Midwives in Providing Holistic Support through Continuity of Care - A Case Study - Nanda Pratama Putri; Rabia Wahdah; Nita Hestiyana; Winda Maolinda (Archives of The Medicine and Case Reports, 2025)
Continuity of care (COC) in midwifery is a model that emphasizes a continuous and trusting relationship between a midwife and a woman throughout her pregnancy, childbirth, postpartum period, and beyond. This approach fosters holistic support, encompassing not only clinical care but also emotional, psychological, and social well-being. This case study explores the role of midwives in providing such comprehensive care within the COC framework. This study presents the case of Mrs. A, a 22-year-old primiparous woman who received COC midwifery care at TPMB Delima Winda Maolinda in Banjarmasin City, Indonesia. The care spanned her pregnancy, childbirth, postpartum period, newborn care, and family planning counseling. Data were collected through direct observation and interviews during midwifery care encounters. The study highlights the various dimensions of care provided, including antenatal check-ups, childbirth assistance, postpartum monitoring, newborn care education, and family planning guidance. It also explores the challenges and benefits of implementing COC in this particular context. In conclusion, this study demonstrates the positive impact of COC midwifery care on maternal and neonatal outcomes. The continuous support and personalized guidance provided by the midwife contributed to Mrs. A's emotional well-being, facilitated informed decision-making, and promoted healthy behaviors. This study underscores the importance of COC in midwifery practice and its potential to enhance the overall quality of care for women and their newborns.